2010
DOI: 10.1007/s10310-009-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of suitable conditions for natural regeneration of Picea jezoensis on fallen logs

Abstract: The abundance of Picea jezoensis, a major conifer tree species in Hokkaido, northern Japan, is currently decreasing due to the lack of suitable conditions for recruitment and intensive harvests. To contribute to the development of sustainable forest management in Hokkaido, suitable substrates for natural regeneration of P. jezoensis were evaluated during a 4-year experimental study using seed additions in a natural coniferous forest. The environmental conditions (moss height, log hardness, extent of the humus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…Well-decomposed fallen logs with moss cover show reduced evaporation and contain water-soluble nutrients (Takahashi et al, 2000). However, seedling densities differ markedly among fallen logs, and not all fallen logs provide safe sites (Takahashi et al, 2000;Narukawa et al, 2003;Iijima & Shibuya, 2010). In addition to the fallen log conditions, genetic factors of each seedling may also impact tree recruitment success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-decomposed fallen logs with moss cover show reduced evaporation and contain water-soluble nutrients (Takahashi et al, 2000). However, seedling densities differ markedly among fallen logs, and not all fallen logs provide safe sites (Takahashi et al, 2000;Narukawa et al, 2003;Iijima & Shibuya, 2010). In addition to the fallen log conditions, genetic factors of each seedling may also impact tree recruitment success.…”
Section: Introductionmentioning
confidence: 99%
“…(Yezo spruce) and Abies sachalinensis Masters (Todo fir) are two major coniferous species in the mixed forests of Hokkaido, northern Japan (Takahashi et al, 2000;Narukawa et al, 2003). Studies have revealed that survival of P. jezoensis and A. sachalinensis seedlings is affected significantly by fallen log conditions, which include the hardness of the log surface (Narukawa et al, 2003;Iijima et al, 2007), moss coverage and/or moss height (Takahashi et al, 2000;Iijima et al, 2007;Iijima & Shibuya, 2010), and light conditions (Iijima & Shibuya, 2010). A microsatellite analysis revealed that P. jezoensis predominantly outcrosses (Tomita et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the positive role of decaying logs is obvious. Decaying logs with moss layer provide moist environment for seedling growth and survival, especially in summer (Iijima & Shibuya 2010). However, A. faxoniana saplings obviously preferred to establish on decaying logs in AF gaps, while distributed relatively evenly among different microsites in A gaps.…”
Section: Discussionmentioning
confidence: 99%
“…and Tsuga spp. (Bace et al 2012), usually rely on elevated surfaces to successfully regenerate (Iijima & Shibuya 2010). In contrast, larger-seeded species, such as Abies spp., with longer tap roots and longer shoots, are resistant to various stresses and generally do not require very specific substrates (Arbour & Bergeron 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of some genera, such as Picea sp., the density of seedlings established on CWD can increase during decomposition and slightly decreases on the most decayed CWD (Mori et al 2004;Zielonka 2006), but less is known about the colonization pattern of other species, such as broadleaves. Previous studies have shown that the enhanced growth and survival of conifers on elevated microsites may be attributed to less competition with shrubs and herbs (Zielonka 2006;Iijima and Shibuya 2010;Ota et al 2012) and a better nutrient and moisture supply (Brunner and Kimmins 2003;Baier et al 2006). However, in mixed broadleaf forests, these mechanisms may act differently for each species because largeseeded species are generally known to be more resistant to environmental stresses (Carlton and Bazzaz 1998;Moles and Westoby 2004).…”
Section: Introductionmentioning
confidence: 99%